The Pope's last crusade: how an American Jesuit helped Pope Pius XI's campaign to stop Hitler - Eisner, Peter (William Morrow, 2013)
Draws on new archival research to examine Pope Pius XI's effort to reject Nazism, discussing how he enlisted the assistance of John La Farge, a virtually unknown American Jesuit, to craft a papal encyclical condemning Hitler's campaign against the Jews